2019
DOI: 10.1186/s43014-019-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and accumulation of di-n-butyl phthalate in six leafy vegetables under hydroponic conditions

Abstract: The uptake and accumulation of din -butyl phthalate (DBP) in six leafy vegetables was investigated under hydroponic conditions. The test vegetables were six varieties of Brassica campestris ssp., including Kangresijiqing (KRSJQ), Xiadiqing (XDQ), Ziyoucai (ZYC), Aijiaohuang (AJH), Shanghaiqing (SHQ) and Gaogengbai (GGB). The root concentration factor (RCF), translocation factor (TF) and transpiration stream concentration factor (TSCF) were calculated in order to compare the difference of uptake and accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It has been reported that organic compounds with logKow values between −1 and 5 are considered mobile under transpiration-driven processes. Therefore, DEHP, with a higher logKow value, was more prone to accumulate in plant roots [28]. In this study, root concentration factor (RCF) values in maize under the mulching years of 0-20 were greater than the value of 1 (Table 2), indicating the accumulation of PAEs and their congeners in maize roots.…”
Section: Tf and Bcf Characteristics Of Paesmentioning
confidence: 52%
See 3 more Smart Citations
“…It has been reported that organic compounds with logKow values between −1 and 5 are considered mobile under transpiration-driven processes. Therefore, DEHP, with a higher logKow value, was more prone to accumulate in plant roots [28]. In this study, root concentration factor (RCF) values in maize under the mulching years of 0-20 were greater than the value of 1 (Table 2), indicating the accumulation of PAEs and their congeners in maize roots.…”
Section: Tf and Bcf Characteristics Of Paesmentioning
confidence: 52%
“…To compare the enrichment and translocation abilities of PAEs, the bioconcentration factor (BCF) and translocation factor (TF) were calculated. BAF includes the root concentration factor (RCF), stem concentration factor (SCF), leaf concentration factor (LCF), and grain concentration factor (GCF) [28]. RCF, SCF, and LCF indicate the ability of plants to absorb compounds from the soil in different organs and can be calculated as follows:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medicinal plants grown in contaminated areas are usually susceptible to concentrating PBT chemicals. Dioxin, dioxin-like polychlorinated biphenyls (PCBs), some indicator PCBs [42,43], metals [44][45][46], and phthalates [47][48][49], among others, are common environmental pollutants that can accumulate in plants in substantial and health-threatening quantities. Exposure to dioxins and dioxin-like substances has been associated with an avalanche of toxic effects during developmental stages, immunotoxicity, and adverse changes in thyroid and steroid hormones and also in reproductive functions [43].…”
Section: Bioaccumulated Toxicantsmentioning
confidence: 99%